Trade and investment in Latin America and Asia: Lessons from the past and potential perspectives from further integration - Berisha-Krasniqi, Valdete; Bouët, Antoine; Estrades, Carmen; Laborde Debucquet, David (International Food Policy Research Institute, 2011)
The last several years have seen an unprecedented cooperation in trade and investment between Asia and Latin America. Since 2003 an average of 2.2 regional trade agreements (RTAs)* per year have been signed between countries of these two regions, and more RTAs are being negotiated. This is an important and relatively new phenomenon, considering that prior to 2003 there was virtually no bilateral RTA between these regions. In light of these trends, this study examines the potential impacts of a free trade agreement (FTA) between Latin America and Asia using the MIRAGE computable general equilibrium (CGE) model of the world economy. The analysis introduces three key modeling innovations: (1) a new way of modeling foreign direct investment (FDI), (2) a new tariff aggregator, and (3) incorporation of bilateral investment treaties (BITs) in the model. These modeling improvements enable us to examine the potential impact of an FTA on FDI, a key aspect of economic relations between Asia and Latin America. The findings in this study show that an FTA between Asia and Latin America would bring benefits to most FTA members, although gains would be higher for Latin American countries as a result of increased investment inflows as well as increased exports to Asia under the FTA.